Czynniki kształtujące ceny ropy naftowej w świecie w roku 2008 - Kaliski, Maciej; Jedynak, Zdzisław (My University, 2009)
Crude oil is the most desired raw material of the world, without which no state can function correctly. In the early 2008, nobody expected that its price would reach such record levels, only to plummet rapidly some time later. However, the imperfection of the competition in this branch of petroleum made that only a threat of disruptions in the production was an impulse to speculation on the world's commercial merchandise exchanges. The purpose of article is to identify the phenomena which take place in the socio-economic environment in the world. The actions taken will make it possible to determine their influence on the level and dynamics of petroleum price changes in 2008. Besides, the article shows the particular consequences for consumers and producers as a result of unfavourable changes in the oil market. It presents available predictions for petroleum prices in 2009-2010.

Ropa naftowa to najbardziej pożądany surowiec świata, bez którego nie może prawidłowo funkcjonować żadne państwo. Z początkiem roku 2008 nie przewidywano, że jej ceny osiągną tak rekordowy poziom, by następnie odnotować ich dramatyczny spadek. Jednakże niedoskonałość konkurencji w tym sektorze sprawił, że jedynie groźba pojawienia się zakłóceń w jej dostawach była impulsem do spekulacji na światowych giełdach towarowych. Celem artykułu jest identyfikacja zjawisk zachodzących w światowym otoczeniu społeczno-gospodarczym. Podejmowane działania umożliwiają określenie ich wpływu na poziom i dynamikę zmian ceny ropy w roku 2008. Ponadto artykuł zawraca uwagę na konsekwencje ponoszone zarówno przez jej odbiorców, jak i dostawców w wyniku niekorzystnych zmian na rynku naftowym. Prezentuje prognozy ceny tego surowca na lata 2009-2010.
Factors shaping world's oil prices in 2008
Wiertnictwo, Nafta, Gaz
Keywords: oil; economy; ropa naftowa; price; ograniczenia; cena; restrictions; gospodarka